2021
DOI: 10.4265/bio.26.167
|View full text |Cite
|
Sign up to set email alerts
|

Virulent and Multiple Antimicrobial Resistance <i>Aeromonas hydrophila</i> Isolated from Diseased Nile Tilapia Fish (<i>Oreochromis niloticus</i>) in Egypt with Sequencing of Some Virulence-Associated Genes

Abstract: Aeromonas hydrophila is a major waterborne pathogen, which induces various diseases in freshwater fish with the capability for zoonotic potential. This study was applied to investigate the prevalence of A. hydrophila in diseased Nile tilapia fish, genetic characterization of the virulence encoding genes (act, aerA, alt, and ast genes) , and antibiotic susceptibility. Out of the 500 diseased Nile tilapia fish samples, 70% (350/500) Aeromonas species were isolated. From which 53.4% (187/350) of Aeromonas hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Pathogenomics is a field of science that uses genomics research to assess the pathogenicity potential of bacteria. However, most of the published epidemiological studies consider only a few genes 13 , 18 , 42 . In the current study, 312 virulence genes were detected in the A. hydrophila pan-genome.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenomics is a field of science that uses genomics research to assess the pathogenicity potential of bacteria. However, most of the published epidemiological studies consider only a few genes 13 , 18 , 42 . In the current study, 312 virulence genes were detected in the A. hydrophila pan-genome.…”
Section: Discussionmentioning
confidence: 99%
“…Every day, fish waste was drained and 50% of the water was replaced with aerated and dechlorinated water from the storage tank. Groups T2, T3, T4, T5, and T6 received 0.1 ml from the prepared vaccines as described previously (Surgha et al 2021 ). The T1 control group received a sterile saline post-intraperitoneal injection (I/P) and stay as a negative control.…”
Section: Experimental Design and Vaccinationmentioning
confidence: 99%
“…However, this can lead to the development of antibiotic resistance and antimicrobial residues in aquaculture (Vivekanandhan et al 2002 ). A recent study by Salah et al ( 2021 ) demonstrated a multi-drug resistance of Aeromonas hydophila chloramphenicol (67.4%), followed by amikacin (51.9%) and gentamicin (47.1%).…”
Section: Introductionmentioning
confidence: 97%
“…The genus Aeromonas has received constant attention from different areas such as aquaculture and veterinary medicine [ 1 , 2 , 3 ], food safety [ 4 , 5 ], and clinical human microbiology [ 6 , 7 ]. Human infections by Aeromonas are more frequent and these strains have an increasing resistance to antibiotics [ 8 , 9 ]. Therefore, it is not only necessary to better understand antibiotic resistance in these species, but their virulence and pathogenicity mechanisms [ 10 ] as well.…”
Section: Introductionmentioning
confidence: 99%